2014
DOI: 10.1159/000362108
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Policy rather than Patient Characteristics Determines Convection Volume in Online Post-Dilution Hemodiafiltration

Abstract: Background/Aims: Sub-analyses of three large trials showed that hemodiafiltration (HDF) patients who achieved the highest convection volumes had the lowest mortality risk. The aims of this study were (1) to identify determinants of convection volume and (2) to assess whether differences exist between patients achieving high and low volumes. Methods: HDF patients from the CONvective TRAnsport STudy (CONTRAST) with a complete dataset at 6 months (314 out of a total of 358) were included in this post hoc analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 28 publications
4
46
1
1
Order By: Relevance
“…Although the CONTRAST study was designed to provide high-volume online hemodiafiltration treatments (8), there was a wide variation in the delivered convective volumes particularly between centers (11). It is well recognized that blood flow and sessional time are important in determining convective exchange (12), but we wished to determine whether there were additional patient or treatment-related factors that were important in achieving higher volume convective exchanges.…”
mentioning
confidence: 99%
“…Although the CONTRAST study was designed to provide high-volume online hemodiafiltration treatments (8), there was a wide variation in the delivered convective volumes particularly between centers (11). It is well recognized that blood flow and sessional time are important in determining convective exchange (12), but we wished to determine whether there were additional patient or treatment-related factors that were important in achieving higher volume convective exchanges.…”
mentioning
confidence: 99%
“…As the duration of the dialysis session is an important determinant of the convection volume achieved, this finding is extremely relevant because it highlights the importance of the convection volume per se [22]. To the best of our knowledge, this is the first study that distinguishes the magnitude of the convection volume from treatment time in a survival analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The results of these studies and a recent meta-analysis of these studies strongly suggest a survival benefit of ol-HDF over HD when high convection volumes (>21.95 l/session) are achieved [20]. Considering the convection volume, it was recently shown that its magnitude is for the main part determined by treatment-related factors, such as session time and blood flow rate, and only for a minor part by patient-related factors, including hematocrit and albumin [21,22]. …”
Section: Introductionmentioning
confidence: 99%
“…Achieving adequate convective volumes may be difficult in patients with limited Q b (patients with catheters or malfunctioning vascular access). However, prescription of Q b is more a matter of treatment policy in each dialysis unit than of the characteristics of the patients themselves [26]. …”
Section: Main Limiting Factors In Achieving High Convective Volume or Qimentioning
confidence: 99%